Mosby's medical dictionary. - 4 0 16; 5 Mosby, Inc. (St. Louis, Mo. : Mosby, 2009)
A comprehensive medical dictionary that contains more than twenty-four hundred illustrations and fifty-one thousand entries that provide information on health care terminology, anatomy, procedures, lab tests, drugs, and other related topics; and includes a color atlas of human anatomy.
Adult;Adult
Keywords: 2 -- 0; 6; English. -- Medicine;Medicine;Medicine -- Dictionaries.;Dictionaries.;Dictionary; 20; 2